Rail steel contact fatigue curves - V. I. Sakalo; A. V. Sakalo (Вестник Научно-исследовательского института железнодорожного транспорта, 2024)
Introduction. The problem of contact fatigue damage of rails has become especially urgent with the intensified railway freight load. An effective method of studying various damage factors is mathematical simulation of the dynamics of motion and accumulation of contact fatigue damage in the rail material. The damage accumulation simulation uses a curve of dependence of the number of wheel loading cycles or design rail section until contact fatigue failure on the value of the selected contact fatigue criterion. This curve could only be obtained in an experiment.Materials and methods. The authors performed bench-scale contact fatigue testing of roller-shape rail steel specimens. The test rig of original design created a load of up to 4000 N on the rollers. The experimental data were processed using the finite element method. The problem of rolling the specimen and the counterbody was solved in the elastoplastic formulation.Results. The authors studied the effects of the size and shape of the contact surfaces for the contact fatigue test specimens on the distribution of contact pressures. They designed and built a roller-on-roller contact fatigue test rig. The researchers tested rail steel specimens for contact fatigue. The results were processed using the finite element method with the plotting of contact fatigue curves of rail steel according to three criteria: combined, Dang Van criterion, amplitude value of maximum shear stress.Discussion and conclusion. The developed methodological approach yielded contact fatigue curves of rail steel. The curves may be used in simulations of the accumulation of contact fatigue damage in the rail material under different axle loads, dynamic loads arising when the rolling stock moves in curves and straight track sections with different rolling profiles of wheels and rails.